Nitrogen metabolism and P-Cu interaction in Cajanus cajan (L.) Millsp contributes to the removal of excess copper in viticulture soil - Mendes, Thalita Fischer Santini [UNESP]; Ferreira, Tassia Caroline [UNESP]; Bomfim, Nayane Cristina Pires [UNESP]; Aguilar, Jailson Vieira [UNESP]; de Camargos, Liliane Santos [UNESP] (Taylor & Francis, 2024)
Copper, a micronutrient in low concentrations, in excess causes negative changes in the growth and development of plants. This study advances understanding in the dynamics of potentially toxic elements in areas with different uses, making it possible to evaluate the potential of C. cajan to remedy/reduce excess Cu in the soil. It was observed that in C. cajan grown in agricultural soil with high P availability, the translocation of Cu to shoot was 5−7 times greater than in grassland and grassland contaminated with Cu, where the preferred allocation for Cu was the root. The efficiency of the photosynthetic and symbiotic system was not affected; but an increase in the concentration of amino acids was observed. Because of considerable accumulation of Cu in the root and shoot, C. cajan was tolerant to a dose of approximately 100 mg kg−1 of Cu in viticulture soil and may be indicated as a phyto-extractor agent for this metal in agricultural soils.
Keywords: physiology; Phytoextraction; pigeon pea; trace element